"Women play sports (just not as well)": Canadian newspapers' coverage of men's and women's sports at the 1999 Pan-American Games. - Mason, Frederick Daniel. (University of Ottawa (Canada), 2000)
This study examined English language Canadian newspapers' coverage of the 1999 Pan-American Games that were held in Winnipeg, Manitoba. Using a methodology that borrowed from the Ricoeurian approach to hermeneutics, a comparison between the coverage of men's and women's sports in five newspapers was made. The study focused on emergent themes in the coverage of men's and women's sports, as well as the identification of descriptors used for men and women athletes. A structural analysis of the text was also made, which included a comparison on the percentage of articles, the percentage of headlines, the percentage of photographs, and the estimated size of articles and photographs. Photographs were also considered a part of the text, and were analyzed in terms of both content and context. Structural results are that women received almost equitable coverage, especially when considered in light of participation rates at the Games. Themes and descriptors of both men and women focused on such things as physicality, emotionality, personality issues, and family life. However, there were differences within the categories of themes that created an image of women athletes who were less experienced and successful in sport, and more emotional than men. Male athletes, by comparison, were presented as more violent, more experienced, and able to be successful in other masculine roles. There was evidence of practices such as ambivalence, infantilization and sexualization towards the women athletes. In conclusion, the study indicate that while women are getting more coverage than ever before, many media practices that marginalize women in sport and set sport off as a male preserve still occur, only they have become more subtle.
Keywords: Canadian Studies.